IDENTIFIKASI STRUKTUR BAWAH PERMUKAAN AREA MANIFESTASI PANAS BUMI AIR PANAS PAGUYANGAN BREBES MENGGUNAKAN METODE GEOLISTRIK DENGAN KONFIGURASI SCHLUMBERGER - Agnis Triahadin; Agus Setyawan (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Geothermal systems as the renewable energy can be indicated by the presence of surface manifestations, such as hot spring water in the Kedungoleng village, Paguyangan Brebes. The hot spring water temperature reaches 740 C is the outflow zone of Mount Slamet geothermal system. Resitivity method is one of the geophysical methods to study subsurface structures based on the electrical properties of rocks. The purpose of this study is to identify the subsurface geological structure in the area of geothermal manifestations Paguyangan based on resistivity method using Schlumberger configuration. Data acquisition process was performed by 5 sounding points with a length of 400 metre for each points. The field data consist of current, voltage and apparent resisitvity were processed using inversion method from IPI2Win software to determine the true resistivity values. Rock lithology and geological structure were analyzed by correlating resistivity and local geological information.The lithology of research area are topsoil with the resistivity is 9,91 to 114 ohm-metre then Sandstones with the resistivity is 0,756 to 6,91 ohm-metre. The next is Shale with the resistivity is 45,1 to 107 ohm-metre and Marl is 31 to 92,3 ohm-metre. The hot spring water is controlled by fault structure which a detected depht approximately 130 metre. Moreover, the Sandstone roles as permeable layer which contains the thermal fluid.Keywords: Fault, geothermal, lithology, Paguyangan, resistivity, and Schlumberger